Pengaruh Streamer Product Knowledge dan Streamer Image Terhadap Minat Beli Konsumen pada Live Shopping - Ananda Rizki Oktavianti; Diah Priharsari; Welly Purnomo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
Live shopping is a shopping activity through live broadcasts shown to the audience in real-time and has now grown rapidly and become popular in the community. Live shopping hosted by broadcasters or often referred to as streamers is usually done to promote sales and can be continued to the purchase transaction process. To foster consumer purchase intention is influenced by consumer trust, and to get consumer trust in streamers in this live shopping activity there are several factors, these factors are streamer product knowledge and streamer image. This study uses the SEM-CB method by distributing questionnaires to 502 respondents and obtaining net data of 433 respondents. From the results of this study, it is found that all three hypotheses are accepted, namely streamer product knowledge affects trust to streamers, streamer image affects trust to streamers, and trust to streamers affects purchase intention.